Pendekatan Sosiologi dalam Model Pembelajaran Smart Classroom di Sekolah - Edi Gunarto; Asep Mulyana (JoIEM (Journal of Islamic Education Management), 2023)
To shed light on sociology's function in managing Islamic educational institutions, an article must be offered on the topic of the sociological approach to smart classroom management. Smart Classroom as a modern learning model has many risks or negative impacts that are likely to keep students away from accomplishing educational objectives. For this reason, an appropriate approach is is required in addressing  the various risks that may occur due to the use of technology in learning. The purpose of this article is to determine what a smart classroom is, what its potential negative effects are, how the smart classroom program is managed, and what sociological approaches can be utilized in this smart classroom program. This article was written using a qualitative approach, with the author accumulating data from various sources of literature, such as existing books and journals. This article concludes that one of the sociological approaches utilized in the smart classroom program is the formulation of a rule, followed by its affirmation and consistent application.